THE EFFECT OF BRAND IMAGE AND PRICE ON CUSTOMER SATISFACTION AND THE IMPACT ON CUSTOMER LOYALTY OF HAIYUM COFFEE - Lazuardi, Mohammad Isma; Sutanto, J.E. (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research aims to determine the effect of brand image and price on customer loyalty through customer satisfaction with Haiyum Coffee as the object of research. The variables used in this study are brand image and price as independent variables, customer satisfaction as a mediating variable and customer loyalty as the dependent variable. The method used is quantitative mediation. The sample used in this study used a non-probability sampling method with a purposive sampling technique and a sample of 120 respondents. Data collection techniques in this study were carried out by distributing questionnaires using a Likert scale. Based on the results of data analysis, it can be concluded that brand image has a significant effect on customer loyalty, brand image has a significant effect on customer satisfaction, price has a significant effect on customer loyalty, price has a significant effect on customer satisfaction, and customer satisfaction has a significant effect on customer loyalty. In addition, there is mediation in the relationship between brand image and customer loyalty through customer satisfaction, and mediation occurs in the relationship between price and customer loyalty through customer satisfaction.